Main Principles of Assessment and Their Significance in Teaching Foreign Languages - Abdumajitova Ra’no Rahimjanovna (Peerian Journals Publishing, 2022)
The article is devoted to the study of the main principles of assessment and its importance in teaching foreign languages, especially in English language classrooms.
Keywords: Assessment; authenticity; practicality; reliability